360 Years of Measles: Limiting Liberty Now for a Healthier Future. Issue 1 (2nd January 2019) - Fadel, Mark
Abstract: The United States Supreme Court has upheld state vaccination mandates as a condition of entry to schools by relying on their police power in protecting public health and safety. Despite this broad authority, many state mandates include exemptions that permit parents to refuse vaccination on behalf of their children for nonmedical reasons, like religious, philosophical, or personal beliefs. A spectrum of these laws currently exists, ranging from California's ban of all nonmedical claims to Ohio's extremely permissive grant of exemptions. This article discusses each of these states' mandates and the relationship between relaxed exemption laws and measles outbreaks using statistical analyses. To curb the spread of this vaccine-preventable disease, states should consider the threat to public health paramount to individual liberty infringement by restricting access to nonmedical exemptions. This approach aligns with a century of case law that has rejected vaccination mandate challenges based on fundamental rights, religious freedom, equal protection, and due process. Now states must act within that authority to safeguard against the persistence of this potentially fatal disease.